Key to the species of Morishitium Wienberg, 1928 (Cyclocoelidae), with the description of a new species from the red-billed blue magpie, Urocissa erythrorhyncha (Boddaert) (Corvidae) from Guizhou Province, People’s Republic of China - Dronen, Norman O.; Tkach, Vasyl V. (Zootaxa, 2014)
The 11 species currently assigned to Morishitium and the new species described herein are divided into the rauschi, straightum and vagum body types, and keys to species are provided. Morishitium urocissae n. sp. is described from the red-billed blue magpie, Urocissa erythrorhyncha (Corvidae), from the Dashahe Nature Reserve, Guizhou Province, southwestern Peoples Republic of China. Morishitium urocissae n. sp. is similar to M. bivesiculatum by having a similar ratio of the width of the pharynx to the width of the oral sucker (1:1.0–1:1.2 compared to 1:1.0) and a similar sized cirrus sac (470–565 long; 3–5% of body length compared to 400; 4%). Both species also have the anterior extent of the vitelline fields reaching the level of the pharynx, which distinguishes them from all other species in the genus that have an oral sucker present and lack a ventral. The new species differs from M. bivesiculatum by having a larger maximum egg size (135 by 70 compared to 127 by 65), uterine loops that overreach the ceca laterally rather than being intercecal, a shorter distance from the posterior testis to the posterior arch of the cyclocoel (70 [0–110] compared to 400), and by being from a magpie from the People’s Republic of China rather than being from a barbet from Sri Lanka. The new species is most similar to M. dumetellae, but differs from this species by having wider eggs (65 compared to 60), a longer body (10,400– 13,350 compared to 8,500), a shorter cirrus sac (470–565; 3–5% of the body length compared to 595; 7%), a smaller ratio of the pharynx to the oral sucker (1:1.0–1:1.3 compared to 1:1.7), more laterally extensive uterine loops (overreaching the ceca compared to being interececal), the anterior extent of the vitelline fields reaching to the level of the pharynx as compared to terminating posterior to the cecal bifurcation, and by being from a magpie from the People’s Republic of China rather than from a catbird from the United States.